2021
DOI: 10.1101/2021.09.10.459834
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Application of The Skin Virome for Human Identification

Abstract: The use of skin virome for human identification purposes offers a unique approach to instances where a viable and statistically relevant human DNA profile is unavailable. The human skin virome may act as an alternative DNA profile and/or an additional form of probative genetic material. To date, no study has attempted to investigate the human virome over a time series across various physical locations of the body to identify its potential as a tool for human identification. For this study, we set out to evalua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 59 publications
(98 reference statements)
2
13
0
Order By: Relevance
“…The libraries were then sequenced as 150 bp paired-end reads on the Illumina HiSeq 2500 platform (Illumina, Inc, San Diego, CA, USA). During that study (5), we identified one participant with a metagenome which consistently showed the presence of a feline papillomavirus and who also self-identified as being an owner of a domesticated house cat.…”
Section: Announcementmentioning
confidence: 99%
See 4 more Smart Citations
“…The libraries were then sequenced as 150 bp paired-end reads on the Illumina HiSeq 2500 platform (Illumina, Inc, San Diego, CA, USA). During that study (5), we identified one participant with a metagenome which consistently showed the presence of a feline papillomavirus and who also self-identified as being an owner of a domesticated house cat.…”
Section: Announcementmentioning
confidence: 99%
“…In a previous study we addressed the diversity and stability of DNA viruses on human skin by sampling three anatomical locations – left hand, right hand, and scalp – over a longitudinal 6-month period for 43 human subjects (5). Briefly, samples were collected using a tandem dry and wet swab technique.…”
Section: Announcementmentioning
confidence: 99%
See 3 more Smart Citations